An optimized Retina Recognition Technique Based on PSO Inspired Algorithm - Suhad Fakhri Hussein (Indian Journal of Forensic Medicine & Toxicology, 2020)
Retina Recognition techniques capture and analyze the vascular patterns on the thin nerve on the backs of an eyeball which process light getting in the pupil. Retinal patterns are extremely distinguishing traits; it cannot be gotten or stolen since there are no two persons have similar patterns of retinal, as well as the features extracted from the retinal image are the most stable and reliable than other biometric features. Therefore, the retina is selected as a robust source in the proposed recognition techniques. In this paper, an optimized technique of retina recognition based on an inspired algorithm is proposed for the authentication purpose in which particle swarm optimization (PSO) inspired algorithm is utilized for extracting features from retinal images. The obtained results from this work declared that the PSO provides an optimized performance with 100% accuracy and 3.5 seconds time-consuming